Reincarnation Daemon: improving dependability on Linux - Ferreira, Alexandre Beletti; Santos, Caio Augusto R. dos; Silva, Fabricio Guerra da (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
This paper presents a tool named Reincarnation Daemon (RD), which is responsible for manage applications that are deemed critical and therefore cannot be permitted to fail. We propose a recovery strategy focused on a largely used operating system (OS), that avoids a complete OS reboot. It targets specific critical applications, restoring them individually in the event of a failure. To achive this, RD monitors process, detects failure and recovers last working image of process, with a minimium overhead and almost everything is done by using POSIX system calls (syscalls). Our approach plans to test the proposed solution in real world problems, comparing it with others fault tolerant strategies.